First report of the use of mucosal swabs of the palatine tonsillar crypt for detection of Mycoplasma bovis in naturally infected calves. Issue 5 (2nd September 2020) - Buckle, KN; Castillo-Alcala, F; Ha, H; Begg, D; McDonald, W; Bingham, P
ABSTRACT: Aims: To compare detection by real-time PCR of DNA from Mycoplasma bovis on mucosal swabs taken from the palatine tonsillar crypt and the mainstem bronchi of clinically asymptomatic calves after slaughter. Methods: We compared the sensitivity of mucosal swabs taken from two sites: the palatine tonsillar crypt and the mainstem bronchi. Paired samples were taken post-mortem at slaughter from 55 clinically well calves from an infected herd and were tested by real-time PCR for the presence of M. bovis -specific DNA. Results: Mycoplasma bovis DNA was detected in 51 palatine tonsillar crypt swabs (92.7 (95% CI = 82.4–98.0)%) and seven mainstem bronchial swabs (12.7 (95% CI = 5.3–24.5)%). All seven calves with positive mainstem bronchial swabs also had positive palatine tonsillar crypt swabs. Conclusions: When compared to mucosal swabs of the mainstem bronchi, mucosal swabs of the palatine tonsillar crypt were seven times more sensitive for the post-mortem detection of M. bovis DNA. The viability of detected M. bovis was not assessed, because any cattle carrying viable or non-viable M. bovis DNA were determined to be a potential risk to eradication. Palatine tonsillar crypt mucosa may be a useful anatomical site for real-time PCR detection of M. bovis DNA in naturally infected calves. More work is needed to define the persistence and viability of M. bovis at this anatomical site. Clinical relevance: The results of this study helped form the basis of surveillance tools used in M. bovis control and eradication efforts. Familiarity with these results may help veterinarians better communicate with their clients about the science behind the eradication efforts.